MENINGKATKAN KEMAMPUAN MENULIS KATA MELALUI METODE GILINGHAM BAGI ANAK KESULITAN BELAJAR KELAS II DI SD NEGERI 05 KAPALO KOTO - SUHELMELI SUHATLI (Universitas Negeri Padang, 2015)
Abstract:This research was conducted due to the problems found in the second grade of SD N 05 Kapalo Koto Indicating that a student did omission on words having KVK-KVK – KVK (Consonant Vocal Consonant – Consonant Vocal Consonant) pattern through dictation. This research then was intented to prove whether the use of Gilingham method could increase the ability of the students with learning difficulties to write words in the second grade of SD N 05 Kapalo Koto Padang. This was an experimental research which applied Single Subject Research (SSR) methid and A-B-A design. The data obtained were analyzed by using visual analysis of graphic and the variables were measured by using percentage technique. In the baseline condition (A1) that consisted of six meetings, it was found out that the mean level was 1,6 % in intervention condition (B) that consisted of nine meeting the mean level was 67,7 %, and in the baseline condition (A2) that consisted of five meetings the mean level was 86 %. The result of within condition analysis and inter-condition analysis showed that the tendency of direction, the tendency of stability, the traces of data and the change of level improved positively. The percentage of the data overlapped in the baseline condition (A1) and in the intervention condition (B) was 0 %, and the percentage of the data overlapped in the baseline condition (A1) and in the intervention condition (B) was 33 %. These results indicated that the smaller the number of the data overlapped, the better the invention affected the change of the target behavior. Based on the research finding it was conclude that the use of Gilingham method could increase the ability of the students with learning disabilities to write words in the second grade of SD N 05 Kapalo Koto Padang.Kata Kuci :Kesulitan Belajar ; kemampuan ; Menulis ; Gillingham